Minimal Intervention in Pediatric Dentistry - Gunda, Sachin; Varma, Narendra (Journal of Orofacial Research, 2013)
Dental caries is an infectious disease, identifying the risk factors and controlling them is important in preventing tooth demineralization. Early recognition of risk factors allows dentist to implement preventive regimes. Prevention includes rebalancing the oral environment to its natural state and preventing oral diseases progression. Once cavitation occurs restoring with minimal intervention technique shall minimize tooth loss and restore function.